Effect of geographic altitude on carbon stock in two physiographic units of the reserved forest of the Universidad Nacional Agraria de la Selva - Reategui Inga, Manuel (2022)
The objective of the research was to evaluate the effect of geographic altitude on the carbon stock in two physiographic units of the Reserved Forest of the Universidad Nacional Agraria de la Selva, Tingo Maria-Huanuco. The methodology used was the field manual for the remeasurement and establishment of plots of the Amazon Forest Inventory Network (RAINFOR), for which 2 hectares were permanently established (one hectare in low and high hills) in which the diameter (greater than or equal to 10 cm) and the height of the trees were measured. Finally, the density of the wood was obtained from previous studies. The pantropical model formula was used to estimate the carbon stock. The results show that geographic altitude significantly affects carbon stock (p < 0.05) in low and high-hill forests, concluding that this may be due to differences in meteorological variables such as precipitation, temperature, and humidity.